2021
DOI: 10.2172/1958739
|View full text |Cite
|
Sign up to set email alerts
|

The Los Angeles 100% Renewable Energy Study (LA100): Chapter 9. Air Quality and Public Health

Abstract: This report is available at no cost from the National Renewable Energy Laboratory (NREL) at www.nrel.gov/publications. U.S. Department of Energy (DOE) reports produced after 1991 and a growing number of pre-1991 documents are available free via www.OSTI.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…In the future anthropogenic emissions scenario, daily average NO x emissions in the city of LA decreased by 63% relative to those in the current day anthropogenic emissions scenario and anthropogenic VOC emissions decreased by 26%, as described in Heath et al (2021). Note that the remaining anthropogenic NO x and VOC emissions in the aggressive electrification scenario include emissions from heavy duty vehicles outside of the San Pedro Bay ports, aircraft, locomotives, and off-road equipment (Heath et al, 2021). Moreover, anthropogenic emissions sources within the innermost domain that were outside of the city of Los Angeles were not electrified.…”
Section: Anthropogenic Emissions Scenariosmentioning
confidence: 94%
See 2 more Smart Citations
“…In the future anthropogenic emissions scenario, daily average NO x emissions in the city of LA decreased by 63% relative to those in the current day anthropogenic emissions scenario and anthropogenic VOC emissions decreased by 26%, as described in Heath et al (2021). Note that the remaining anthropogenic NO x and VOC emissions in the aggressive electrification scenario include emissions from heavy duty vehicles outside of the San Pedro Bay ports, aircraft, locomotives, and off-road equipment (Heath et al, 2021). Moreover, anthropogenic emissions sources within the innermost domain that were outside of the city of Los Angeles were not electrified.…”
Section: Anthropogenic Emissions Scenariosmentioning
confidence: 94%
“…It should be noted that while these emissions projections are for the year 2045, the future anthropogenic emissions simulations do not consider changes in temperature from global warming and instead use the same meteorology as the current day anthropogenic emissions simulations. In the future anthropogenic emissions scenario, daily average NO x emissions in the city of LA decreased by 63% relative to those in the current day anthropogenic emissions scenario and anthropogenic VOC emissions decreased by 26%, as described in Heath et al (2021). Note that the remaining anthropogenic NO x and VOC emissions in the aggressive electrification scenario include emissions from heavy duty vehicles outside of the San Pedro Bay ports, aircraft, locomotives, and off-road equipment (Heath et al, 2021).…”
Section: Anthropogenic Emissions Scenariosmentioning
confidence: 95%
See 1 more Smart Citation
“…Both PM2.5 and NO2 traffic air pollutants cause health issues including asthma, cardiovascular disease, respiratory disease, and premature mortality (HEI 2022). We model health benefits that could accrue to city residents as a result of emissions reductions from electrifying trucks in selected TAQ-DAC and non-DAC tracts using a methodology similar to that used in the LA100 study (Heath et al 2021). The basis of our analysis relies on the EPA's Environmental Benefits Mapping and Analysis Program (BenMAP) model (Sacks et al 2018), with updated health effect estimates identified in the most recent meta-analysis conducted by a Health Effects Institute panel (HEI 2022).…”
Section: Health Impacts Modeling and Environmental Justice Analysismentioning
confidence: 99%
“…Both PM2.5 and NO2 traffic air pollutants cause health issues including asthma, cardiovascular disease, respiratory disease, and premature mortality (HEI 2022). We model health benefits that could accrue to city residents as a result of emissions reductions from electrifying trucks in selected TAQ-DAC and non-DAC tracts using a methodology similar to that used in the LA100 study (Heath et al 2021). The basis of our analysis relies on the EPA's Environmental Benefits Mapping and Analysis Program (BenMAP) model (Sacks et al 2018), with updated health effect estimates identified in the most recent meta-analysis conducted by a Health Effects Institute panel (HEI 2022).…”
Section: Health Impacts Modeling and Environmental Justice Analysismentioning
confidence: 99%